The determinant of customer choice of conventional bank in Majlis Perbandaran Batu Pahat, Johor / Norhazlinda Adam and Siti Najihah Mohd Sukiman - Adam, Norhazlinda; Mohd Sukiman, Siti Najihah (Faculty of Business and Management, 2013)
People were found to be more precise on choosing the best bank services. Therefore, it is important to identify the determinant of choosing conventional bank as a lot of competitor that exists in the market for financial services presents a big resistance to the profitability of the bank. However, there is lack of research on the determinants of factor affecting customer choice of conventional bank. Six determinants are identified which are follows: reliability, convenience, assurance, value added service, accessibility and responsiveness. Questionnaires were distributed to the 150 respondents. The sampling procedure adopted was stratified random sampling. The data obtain were analysed using SPSS 20.0 which involve scale reliability, frequency analysis, descriptive analysis and Pearson Correlation Coefficient. The result indicates that for responsiveness, reliability, convenience, accessibility and value-added service have a moderate significant relationship that influences the customer choice of conventional bank. Moreover, assurance becomes the high significant relationship with the customer choice of conventional bank. This study contributes to the literature on choosing a bank service. The finding achieved in this study will be of interest for bank in order to increase their profitability for long term.